Stosunek Demokratycznego Ruchu na rzecz Przebudowy oraz Mołdawskiego Frontu Ludowego do władz komunistycznych i suwerenności Mołdawii w latach 1989–1991 - Kubiak, Antoni P. (Instytut Historii PAN, 2025)
This article presents the evolution of the attitude of the Democratic Movement for Reconstruction, and the Moldovan People’s Front founded on it towards the Communist authorities of Moldova and the Soviet Union, as well as towards Moldovan sovereignty. The documents issued by the above organisations and the archives of the Communist Party of Moldova were the sources on which I based my research. The chronological scope of this thesis is between 1988 and 1991, i.e. from the founding of the Democratic Movement for Reconstruction until Moldova declared independence. I aimed to show how, over the years, both organisations radicalised their demands and their views on Moldova’s presence in the structures of the Soviet Union.
p. 5-220
Summary in English.
Keywords: Democratic Movement for Reconstruction; Moldovan Popular Front; Communist Party of Moldova; Mikhail Gorbachev; Gorbachev, Mikhail Sergeevich; Moldova; Soviet Union - politics and governments - 20th c.